An Opportunity to Grow or a Label? Performance Appraisal Justice and Performance Appraisal Satisfaction to Increase Teachers’ Well-Being - Dal Corso, Laura; De Carlo, Alessandro; Carluccio, Francesca; Girardi, Damiano; Falco, Alessandra (Frontiers in Psychology, 2019)
Performance management is a key factor to enhance professional development and improve teaching quality. This process is successful only if teachers perceive it as fair, clear, and effective: namely, if it is satisfying. Carefully considering teachers’ attributions in the performance appraisal process is fundamental to better clarify the relations between performance management and positive individual outcomes. Therefore, this study aims to investigate the effects of perceived performance appraisal justice on teachers’ well-being, in terms of job performance, job satisfaction, and life satisfaction, hypothesizing the mediation role of performance appraisal satisfaction. Data from a sample of Italian teachers were analyzed through structural equation modeling. Results confirm the mediation role of performance appraisal satisfaction. In particular, perceived performance appraisal justice was positively associated to performance appraisal satisfaction, which, in turn, was positively associated with job performance, job satisfaction, life satisfaction. Consequently, performance appraisal satisfaction totally mediated the relations between performance appraisal justice and the outcomes considered. Findings are relevant for two reasons. First, they contribute to better understanding the performance management process in educational settings ̶ an issue requiring further attention. Second, they contribute to highlighting the importance of performance management efficacy, which is essential not only to improve individual well-being but also to enhance teaching quality.